International Current Affairs in Chilean Translation and Interpreting Programs: Current Scenario and Post-Pandemic Curricular Challenges [Actualidad Internacional en Los Programas de Traducción E Interpretación en Chile: Escenario Actual y Desafíos Curriculares Pospandemia] - Ahumada-Figueroa, M; Basaure-Cabero, R (Pontificia Universidad Catolica de Chile, 2022)
Due to the global crisis caused by the COVID-19 pandemic, translation and interpretation education faces an uncertain future, reinforcing the idea of a discipline immersed in an interconnected world and aware of international context issues. On this basis, the article explores translation training and international context relation. In addition, it suggests mechanisms to adapt the educational approach to a post-pandemic scenario in which future professionals will develop their professional paths. From a methodological point of view, the article analyzes the relevance of thematic knowledge regarding international relations within translation competence training and the practical experience of Chilean institutions up to the outbreak of the pandemic. Subsequently, the article supports curricular redesign regarding this area, considering new national and international scenarios in which the post-pandemic translation practice will be developed. Finally, it presents a pedagogical proposal that considers the integration of international thematic contents related to theory, concepts, and international scenarios, and also the use of technology given current possibilities. This curricular proposal introduces pandemic context in translation and interpretation-related research in Chile. The paper concludes by calling attention to promoting initiatives in this area through virtualized education processes, reinforcing this aspect of translation competence for a changing global scenario, based on the collaborative work among national and international programs for translation and interpreting education. © 2022 Pontificia Universidad Catolica de Chile. All rights reserved.